331 FEASIBILITY OF BEDSIDE FRACTURE RISK ASSESSMENT IN HOSPITALIZED OLDER WOMEN. (1st January 2006) - Ryder, K. M.; Kessler, L.; Baker, S.; Jones, C.; Shorr, R. I.
Abstract : Background: Osteoporosis is underdiagnosed and undertreated, and hospitalization for any cause in older women increases the risk of subsequent hip fracture. We sought to determine whether bedside osteoporosis screening is acceptable to hospitalized women, and whether osteoporosis screening influences diagnostic or treatment decisions following discharge. Methods: Hospitalized older women, who were not being treated for osteoporosis, were offered screening using calcaneal ultrasound (Hologic). In addition, participants received personalized fracture risk information and low-literacy education material. Patients identified a primary care physician and were encouraged to ask their doctor about definitive diagnosis and treatment. The primary care doctor also received the patient's fracture risk information, as well as educational material and helpful osteoporosis Web sites. Response was assessed using a telephone interview 2 months after discharge. Results: 18 women met study criteria. The mean age was 76 and the majority were black (77.8%). The most common admission diagnoses were congestive heart failure (n = 6) and emphysema (n = 5). One-third (n = 6) were receiving corticosteroids, and nearly two-thirds (n = 11) had fallen within 12 months of hospital admission. The median T-score was negative 2.2 (range 24.2 to 0). Of the 18, 10 thus far have completed telephone interviews. One participant had died. Of the remaining 9, 8 made at least 1 behavioral change. Only 1 recalled speaking with their doctor at follow-up appointment about fracture risks, received a DXA, and started a prescription antiresorptive. However, 3 women initiated calcium and vitamin D upon the recommendation of their physicians, 1 initiated calcium and Vitamin D on her own, and 4 more increased dairy intake by an estimated 600 mg/day. Four reported making home safety changes, 6 initiated physical therapy or exercises, and 4 reported new/increased use of their walking aid. Conclusion: Bedside fracture risk assessment and education are feasible in hospital settings and identify women with low bone density and fracture risks. Women identified as having risks for fracture using this approach undertake measures to reduce fracture risk. Supported by the Methodist Foundation.